Effect of limited ischemia time on the amount and function of mitochondria within human skeletal muscle cells - Jawhar, Ahmed; Ponelies, Norbert; Kasper, Lydia (European journal of trauma and emergency surgery, 2016)
Introduction The clinical success of total knee arthroplasty (TKA) depends substantially on the quadriceps muscle function. A frequently applied thigh tourniquet during TKA may induce ischemia related injuries to quadriceps muscle cells. Animal limb muscles subjected to 2-5 h ischemia revealed dysfunctional mitochondria, which in turn compromised the cellular bioenergetics and increased the level of reactive oxygen species. The hypothesis of the present study was that tourniquet application during TKA for 60 min (min) affects the amount and function of mitochondria within musculus vastus medialis cells.Materials and methodsIn a randomized clinical trial, 10 patients enrolled to undergo primary TKA. The patients were randomly assigned to the tourniquet (n = 5) or non-tourniquet group (n = 5) after obtaining a written informed consent. For each of the groups, the first muscle biopsy was harvested immediately after performing the surgical approach and the second biopsy exactly 60 min later. All biopsies (5 × 5 × 5 mm) 125 mm3 were harvested from musculus vastus medialis and snap-frozen in liquid nitrogen. The biochemical analysis of the prepared muscle tissues included the measurement of activities of mitochondrial respiratory chain enzyme complexes I-III and citrate synthase.ResultsTourniquet-induced 60 min ischemia time did not significantly change the activities of the mitochondrial respiratory chain enzymes complexes I-III of the skeletal muscle cells. The citrate synthase activities found to be not significantly different between both groups.ConclusionsThe use of tourniquet during TKA within a limited time period of 60 min remained without substantial effects on the amount and function of mitochondria within human skeletal muscle cells.